Статер Емінака з передмістя Ольвії - Івченко, А.В. (Археологія, 2013)
Публікується перша знахідка статера Емінака з передмістя Ольвії. Статеры Эминака являются крайне малочисленной категорией монет V в. до н. э. Большинство из них найдены случайно и точное место их открытия неизвестно. В 2012 г. впервые обнаружена такая монета в северном предместье Ольвии (верховья Заячьей балки). В целом анализ локализации таких находок показывает, что, несмотря на их малочисленность, они встречаются на всей территории Ольвийского полиса. Staters of eminako are extremely scanty category of the 5th c. BC coins. Most of them are found accidentally and the exact location of their discovery is not known. In 2012, such coin was found in the northern outskirts of olbia (upper reaches of zaiacha gully) for the first time. As a whole, the analysis of mapping of such finds shows that, despite their small number, they are found throughout the olbian polis territory.